THE OBLIGATION TO INFORM ONE ANOTHER OF THE INSURANCE CONTRACTIG PARTIES. LIMITS AND CONTENT OF THE OBLIGATION, FROM THE POINT OF VIEW OF EACH OF THE CONTRACTING PARTIES. - Ștefan Matei DĂNILĂ (Challenges of the Knowledge Society)
In contractual relationships, in general, and as regards the insurance contract, in particular, the obligation to inform one another is of particular importance, all the more so as it is an effective means of protection for both contracting parties. The obligation of the professional to provide advice to the user of insurance services in order to conclude the contract requires the observance of certain principles such as loyalty and good faith and is carried out, as a rule, by insurance intermediaries. The obligation to advice of the insurer refers, and at the same time is limited, exclusively to the framework of the insurance operation, without involving external aspects and that are presumed to be known by all. According to some opinions, the obligation to advice is distinguished from the obligation to provide information, the content of which is distinct and refers to the contractual relationship and not to the pre-contractual relationship. Also, the other contracting party, the insured, has the obligation to inform the insurer, being mandatory that the insured acts in good faith when providing the information required by the insurer, information that is considered by the insurer important when taking over and quantifying the risk. The insurance contracts must be executed with the utmost good faith. The aspects related to hiding certain key elements are often found in insurance contracts. Failure to inform or distortion of the facts is a violation of the obligation to inform, involving, together with fraud, serious consequences in the execution of the contract by the insured. All these aspects will be the subject of our analysis, presented within this article.